Effects of laparoscopy, laparotomy, and respiratory phase on liver volume in a live porcine model for liver resection - Kenngott, Hannes Götz; Nickel, Felix; Preukschas, Anas; Wagner, Martin; Bihani, Shivalik; Özmen, Emre; Wise, Philipp; Bellemann, Nadine; Sommer, Christof-Matthias; Norajitra, Tobias; Graser, Bastian; Stock, Christian; et al. (Surgical endoscopy and other interventional techniques, 2021)
Hepatectomy, living donor liver transplantations and other major hepatic interventions rely on precise calculation of the total, remnant and graft liver volume. However, liver volume might differ between the pre- and intraoperative situation. To model liver volume changes and develop and validate such pre- and intraoperative assistance systems, exact information about the influence of lung ventilation and intraoperative surgical state on liver volume is essential.
Gesehen am 14.10.2021